2016
DOI: 10.1016/j.juro.2016.03.135
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Distension Increases Blood Flow in Pain Related Brain Structures in Subjects with Interstitial Cystitis

Abstract: Purpose In Healthy Control subjects (HCs) certain brain regions of interest (ROIs) demonstrate increased regional cerebral blood flow (rCBF) in response to painful stimuli. The effect of bladder distension on arterial spin label-functional MRI (ASL-fMRI) measures of rCBF within ROIs was examined in subjects with Interstitial Cystitis (ICs). Methods and Materials Female ICs (n= 11) and HCs (n=11) underwent three brain perfusion scan studies using ASL-fMRI: with a full bladder; with an empty bladder; and while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 32 publications
(46 reference statements)
2
30
0
Order By: Relevance
“…33 Recent brain imaging studies in patients with chronic bladder pain have reported hemispheric asymmetries in amygdala structural integrity, anatomical connectivity, and functional activity. 1,3,16,27 These data are noteworthy because noxious bladder signals are presumed to equally engage both sides of the brain through bilateral peripheral and spinal afferents. 10,36 …”
Section: Introductionmentioning
confidence: 95%
“…33 Recent brain imaging studies in patients with chronic bladder pain have reported hemispheric asymmetries in amygdala structural integrity, anatomical connectivity, and functional activity. 1,3,16,27 These data are noteworthy because noxious bladder signals are presumed to equally engage both sides of the brain through bilateral peripheral and spinal afferents. 10,36 …”
Section: Introductionmentioning
confidence: 95%
“…83,84 Regions in this network frequently identified with both functional and structural abnormalities in patients with IC/BPS include sensorimotor regions, such as primary somatosensory cortex, supplementary motor cortex, and the thalamus, but also regions deeply engaged in the modulation of emotions, such as the cingulate, insula, and amygdala. [16][17][18][20][21][22][23][24]85,86 In our rodent model, WAS animals compared with SHAM demonstrated a decreased pressure threshold and VMR threshold triggering the voiding phase. Our prior study 29 demonstrated that WAS compared with SHAM animals demonstrated significant changes in cerebral activation during passive bladder distension.…”
Section: Discussionmentioning
confidence: 75%
“…This posterior midline cortical region contributes to pain and to micturition circuits, shows stress effects, and has been reported to demonstrated altered functionality in patients with IC/BPS. 19,85 Given the actions of CTX on the glutamate transporter, our results suggest the possibility of glutamatergic pharmacologic strategies in modulating stress-related bladder dysfunction.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Unlike PET scans that require the administration of radioactive intravenous contrast to measure cerebral perfusion, ASL uses inverted proton spins of magnetically labeled water in the blood as a tracer. Using continuous ASL, Deutsch et al reported quantitative increases in absolute rCBF in several regions of the brain involved in the pain matrix in women with interstitial cystitis [ 8 ]. However, cerebral perfusion changes associated with urinary urgency in women with OAB have not been quantified.…”
Section: Introductionmentioning
confidence: 99%